2000
DOI: 10.1046/j.1469-8137.2000.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane electric potential difference of germ tubes of arbuscular mycorrhizal fungi responds to external stimuli

Abstract: Measurements of the electric potential difference across the hyphal wall and the cell membrane were made on external hyphae of three species of arbuscular mycorrhizal fungus Gigaspora margarita, Scutellospora calospora and Glomus coronatum and on germ tubes of Gi. margarita. The values of transmembrane electric potential difference recorded ("k40 mV) are less negative than those previously reported from hyphae of arbuscular mycorrhizal fungi closely associated with roots and from filamentous fungi. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
7
20
0
Order By: Relevance
“…These fluxes are correlated with the direction and magnitude of electrical currents described previously for each germination stage of AM spores (Berbara et al 1995). In addition, the electrical membrane potential (Em) across the spore wall from non-germinated spores was found to be more negative than in germinated spores (Ayling et al 2000). On the other hand, Chloride (Cl − ) displays the inverse direction of H + , going out in regions where H + goes in, and vice versa (Fig.…”
Section: Proton Fluxes and The Regulation Of Ion Uptakesupporting
confidence: 70%
See 2 more Smart Citations
“…These fluxes are correlated with the direction and magnitude of electrical currents described previously for each germination stage of AM spores (Berbara et al 1995). In addition, the electrical membrane potential (Em) across the spore wall from non-germinated spores was found to be more negative than in germinated spores (Ayling et al 2000). On the other hand, Chloride (Cl − ) displays the inverse direction of H + , going out in regions where H + goes in, and vice versa (Fig.…”
Section: Proton Fluxes and The Regulation Of Ion Uptakesupporting
confidence: 70%
“…For instance, measurements of total membrane electric potential carried out by Ayling et al (2000) revealed Em values of germ tubes of G. margarita around −40 mV, a value much lower than −200 mV in Neurospora crassa (Miller et al 1990), −160 mV in Achlya bisexualis (Kropf et al 1984) and −132 mV in pollen tubes (Weisenseel et al 1975). Likewise, Berbara et al (1995), using a one-dimension vibrating voltage probe, measured small total currents (~20 μA cm -2 ) at the tip of germ tubes of G. margarita, which were also much weaker than that found in clover roots and in other fungi (Ayling et al 2000). Such characteristics could be related to the AM fugal H + pumping capacity, since the magnitude of the H + fluxes detected in the AM hyphae was also much lower than that observed in polarized plant cells, such as pollen tubes .…”
Section: Electrophysiological Responses As a Component Of Signaling Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional information on the Pi uptake system can be derived from measurements of the transmembrane potential difference (PD) of germ tubes and extraradical hyphae. Values are rather low [around -47 mV, (Ayling et al, 2000)], compared with other organisms, but using this value and an external Pi concentration of 35 µM gives an H + /H 2 PO 4 -stoichiometry of 2.33. This is higher than the most generally accepted ratio of 2.0, but within the range of published values.…”
Section: Fungal P Uptake Compartmentation and P Poolsmentioning
confidence: 97%
“…In addition, the cytosolic pH was more alkaline when G. rosea was growing in the vicinity of a host root (Jolicoeur et al, 1998). In Gigaspora margarita, transmembrane electric potential difference became more negative when plant root extracts were added to the medium (Ayling et al, 2000).…”
mentioning
confidence: 99%